Dampak Pertambangan Emas Tanpa Izin Terhadap Kualitas Air Permukaan - Sofia Wantasen; Frangky J Paat; Tommy B Ogie (Seminar Nasional Lahan Suboptimal, 2021)
Wantasen S, Paat FJ, Ogie TB. 2021. Impact of illegal gold mining on surface water quality. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 228-232.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Environmental indicators due to the impact of illegal gold mining can be seen in the decline in surface water quality. It is necessary to conduct research to obtain data and information on the extent to which the gold mining process activities carried out by the community without management are at risk of environmental damage. This study aims to examine the impact of illegal gold mining on the decline in surface water quality. The research method is field observation of illegal gold mining activities and sampling of surface water quality is carried out using the composite method in the Lobok river in Lanut village. The data obtained is data for 2017 and 2019. Analysis of total suspended solids (TSS) in surface water bodies in the laboratory. Data analysis using the Graphic Method and comparing with the Quality Standards according to PP no. 22/2021 Class II. The results showed that the concentration of TSS in the Lobok river 2017 is 24,800 and 2019 is 92,700 mg/l did not meet the quality standard requirements, indicating that it had experienced high ecological pressure.